Surgery of colorectal lung metastases : Results of a survey in Germany - Dudek, Wojciech; Schreiner, Waldemar; Stapel, Philipp; Vassos, N.; Grützmann, Robert; Sirbu, Horia (Chirurg, 2017)
There is no evidence from randomized trials on the prognostic significance of pulmonary metastasectomy of colorectal cancer. The objective of this study was to assess the current criteria for indications, preoperative diagnostics and preferred operative techniques of pulmonary metastasectomy in Germany.An anonymous survey was carried out in 239 German centers performing thoracic surgery in October 2015.Chest computed tomography (CT, 98%), liver CT (62%), pelvis CT (39%) and fluorodeoxyglucose positron emission tomography (FDG-PET, 37%) were used by the respondents (65% of participants) for preoperative staging. Pulmonary metastasectomy was most commonly performed for solitary lung metastasis without extrathoracic disease (96%), >1 ipsilateral lung metastases without extrathoracic disease (94.8%), solitary lung metastasis with resectable hepatic metastases (92%) and resectable bilateral lung metastases without extrathoracic disease (91%). Of the respondents 95% performed open lung metastasectomy, 82% video-assisted thoracic surgery, 18% radiofrequency ablation, 53% used laser-assisted open resection and 46% indicated that there was no scientific consensus on pulmonary metastasectomy.The majority of respondents performed pulmonary metastasectomy for solitary and multiple, unilateral and bilateral lung metastases without extrathoracic disease and/or local recurrence of primary tumors. The coexistence of resectable liver metastases was not an absolute contraindication for surgery. Of the respondents 46% expressed the need for prospective randomized studies to improve the evidence on pulmonary metastasectomy for colorectal cancer.
EVALuna2:15251